Solve for x: 8x - 3 = 5(2x + 1)

Asked
1 year ago

Viewed
184095 times

**Answer:**

x = - 4

**Step-by-step explanation:**

Given

8x - 3 = 5(2x + 1) ← distribute

8x - 3 = 10x + 5 ( subtract 10x from both sides )

- 2x - 3 = 5 ( add 3 to both sides )

- 2x = 8 ( divide both sides by - 2 )

x = - 4

**Answer:**

x = - 4

**Step-by-step explanation:**

8x - 3 = 5(2x + 1)

8x - 3 = 5 × 2x + 5 × 1

8x - 3 = 10x + 5

8x - 10x = 3 + 5

- 2x = 8

2x = - 8

x = (- 8)/2

**x**** ****=**** ****-**** ****4**

**Thus****,**** **The value of x is **-4**

__-TheUnknown____S____cientist__

Solve for e

Enter your username or email to reset your password. You will receive an email with instructions on how to reset your password. If you are experiencing problems resetting your password contact us or send us an email